Nationally determined contributions to the 2015 Paris Agreement goals: Transparency in communications from developing country Parties - Mulatu, Kalkidan A.; Nyawira, Sylvia S.; Herold, Martin; Carter, Sarah; Verchot, Louis (Informa UK Limited, 2024)
The goals of the Paris Agreement (PA) on collectively managing climate change can only be reached if all parties to the United Nations Framework Convention on Climate Change (UNFCCC) commit to actions supporting their Nationally Determined Contributions (NDCs). Developing-economy nations play a crucial role in reaching the PA targets, particularly in the Agriculture, Forest, and Other Land Uses (AFOLU) sector. However, developing country Parties also face several constraints in tracking and communicating progress towards their climate policy targets and implementation of their NDCs. The operationalization of Biennial Transparency Report (BTR) and Enhanced Transparency Framework (ETF) under the PA will bring stricter reporting timeframes and advanced transparency for all parties. With these requirements rapidly coming into force, addressing reporting gaps is now a pressing priority. The present study analyzes the NDCs, and Biennial Update Reports (BURs) submitted by developing country Parties under the UNFCCC. In an illustrative exercise, our in-depth analysis concentrates on reporting on the AFOLU sector and identifies issues impeding a comprehensive and comparable Global Stock Take (GST): (i) issues of consistency in reporting timeframes (ii) issues in transparency of reporting on mitigation sectors and on relevant progress indicators (iii) incomparability of methodological approaches proposed and used, and (iv) the implications of limited national capacity for transparent reporting. The UNFCCC and developed country Parties now have the opportunity of providing specialized support for developing country Parties. This could include tailored guidance to address gaps in both greenhouse-gas (GHG) emissions accounting, and reporting challenges, to ensure consistent, comprehensive, and transparent reporting to reinforce capacities moving forward following the next GST.